P585 Examining faecal incontinence and its impact on health-related quality of life in patients with Crohn's perianal fistulas: results from a multi-country burden of illness study. (21st January 2022) - Karki, C; Athavale, A; Hantsbarger, G; Lee, K; Milicevic, S; Perovic, M; Raven, L; Sajak-Szczerba, M; Sharpe, E; Tozer, P
Abstract: Background: Perianal fistulas (PAF) are a common complication associated with Crohn's disease (CD), and patients with Crohn's perianal fistulas (CPF) are more likely to experience faecal incontinence (FI) than patients with CD without PAF (non-PAF CD). A global study was conducted to assess the burden of illness in patients with CPF compared with patients with non-PAF CD. Here, we present data on the level of FI and its impact on quality of life (QoL). Methods: This cross-sectional study was conducted in seven countries (France, Germany, Spain, UK, Canada, Australia and Japan) in patients aged ≥21 and ≤90 years with self-reported physician-diagnosed CD. Patients were classified as having non-PAF CD (cohort 1) or CPF without PAF-related surgery (cohort 2) or CPF with PAF-related surgery (cohort 3). Validated, general and disease-specific patient-reported outcome data were collected using a 45-min IRB/EC-approved web-enabled questionnaire. The level of FI was evaluated using the Revised Faecal Incontinence Score (RFIS) (1–20 scale, 0 = no incontinence, 4-week recall period) and the impact of FI on QoL in patients who had experienced FI using the Fecal Incontinence Quality of Life (FIQL) (1–5 scale, 1 = lower QoL). Data were analysed using descriptive statistics. Results: Of the 929 patients recruited (cohort 1, n = 620; cohort 2, n = 174; cohort 3, n = 135), 58–69% were male and 55–67% were aged 21–40 years across all cohorts. A significantly higher proportion of patients in cohort 3 than cohort 1 had severe Crohn's disease as classified by a physician (18% vs 9%, respectively; p < 0.05). Overall, 47% of patients reported experiencing FI and completed both the RFIS and FIQL. Significantly higher proportions of patients in cohorts 2 and 3 had experienced FI than in cohort 1 (59% and 59% vs 40%, respectively; p < 0.05), and a significantly higher proportion were currently experiencing FI in cohort 3 than in cohorts 1 and 2 (69% vs 37% and 45%, respectively; p < 0.05). Mean RFIS scores were significantly higher (worse) in cohorts 2 and 3 than cohort 1 (9.5 [ p < 0.05] and 10.6 [ p < 0.001] vs 8.2, respectively). Patients in cohort 2 had significantly lower (worse) FIQL scores than those in cohort 1 across three FIQL domains (lifestyle [2.2 vs 2.4], depression/self-perception [2.1 vs 2.3], embarrassment [2.2 vs 2.4]; p < 0.05), whereas patients in cohort 3 only reported significantly lower FIQL scores compared with cohort 1 in the embarrassment domain (2.2 vs 2.4; p < 0.05). Conclusion: In this study almost half of the patients experienced faecal incontinence. Among those who experienced faecal incontinence, patients with PAF experienced a significantly higher impact on their quality of life compared with patients without PAF.